Dampak Pembelajaran Lintas Jurusan pada Program PMM-MBKM - Amar Jufri; Rizka Harfiani (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to analyze the negative and positive impacts of cross-department learning (LINJUR) in the Independent Student Exchange Program 3 (PMM3) at the University of Muhammadiyah Malang (UMM). Through a qualitative approach, this study highlights the challenges faced by PAI students who take part in the program, such as information discrepancies, difficulties in academic adaptation, language and cultural barriers, and difficulties in building relationships. However, there are also positive impacts, such as broadening of horizons and knowledge, development of communication and interpersonal skills, personal growth and adaptation skills, building networks and career opportunities, and increased confidence and initiative. Implications of these findings include the need to provide more accurate information on available courses, better support in the adaptation process, and further exploration of strategies that can maximize the benefits of cross-departmental student exchange programs. This research provides a deep understanding of students' experiences in facing challenges and taking advantage of opportunities in the context of cross-department learning, as well as providing a basis for further development in the implementation of PMM programs.